Balancing Democracy and Adz-Dzari'ah Principles: Legal Reasoning on Term Limits for Political Party Chairpersons in Indonesia - Billah, Mu'tashim; Rahma, Vivi; Yudha, Alda Kartika (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2023)
This study explores the issue of term limits for political party chairpersons from the perspective of democracy and the principles of az-zari'ah. In 2022-2023, there was a surge in lawsuits to the Constitutional Court regarding the absence of rules regarding the term of office of political party chairpersons in Indonesia. The number of lawsuits shows that the absence of such rules has caused considerable problems, both within and outside political parties and the state. Various political diseases have become increasingly apparent, such as the perception that public officials only follow the direction of party leaders (bossism), and this has the potential to lead to abuse of power by political party chairmen in the context of public policy. Using a qualitative literature review methodology, this study uses a comparative philosophical approach, namely by paying attention to the principles of democracy and applying methods derived from az-zari'ah. Both of these are used because, on the one hand, Indonesia is a country that applies the principles of democracy; on the other hand, many Indonesian people believe in the truth of Islamic law, including the principles of az-zari'ah. It was found that, from the perspective of az-zari'ah, the term of office of the party chairman must be limited (closed) so as not to become a vehicle for political disease. By Az-zari'ah, limiting the term of party leaders becomes a crucial matter, as it helps mitigate potential harms that may arise in the absence of such limitations. Meanwhile, from a democratic perspective, it also has the same value implications, namely the need to limit the term of office of the chairman. Democracy has the basic function of limiting political power in a person and not expanding or giving unlimited power like a monarchical system. This is because democracy believes that power tends to corrupt, and absolute power corrupts. So, since Indonesia uses the philosophy of democracy in its country, every political institution, in this case, political parties, must abide by the same rules.